2022
DOI: 10.1371/journal.pone.0263553
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-induced protein carbonylation promotes deterioration of physiological activity of wheat seeds

Abstract: During the seed aging process, reactive oxygen species (ROS) can induce the carbonylation of proteins, which changes their functional properties and affects seed vigor. However, the impact and regulatory mechanisms of protein carbonylation on wheat seed vigor are still unclear. In this study, we investigated the changes in wheat seed vigor, carbonyl protein content, ROS content and embryo cell structure during an artificial aging process, and we analyzed the correlation between protein carbonylation and seed v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Protein carbonylation is a fingerprint of oxidative stress of biological systems and is considered the most damaging type of modification of proteins. 35 The aging of apple embryos, 36 the senescence of root nodules in beans, 16 and the loss of seed vigor 37 are correlated with the buildup of protein carbonylation. The carbonylated proteins are finally degraded or accumulate in cells, which causes dysfunction of cells exposed to ROS.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Protein carbonylation is a fingerprint of oxidative stress of biological systems and is considered the most damaging type of modification of proteins. 35 The aging of apple embryos, 36 the senescence of root nodules in beans, 16 and the loss of seed vigor 37 are correlated with the buildup of protein carbonylation. The carbonylated proteins are finally degraded or accumulate in cells, which causes dysfunction of cells exposed to ROS.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Researchers concluded that increased As accumulation drastically enhanced lipid peroxidation and protein carbonylation, affecting rice plants’ yield. Likewise, ROS-mediated protein carbonylation of enzymatic and non-enzymatic antioxidants invariably decreases seed vigor and other physiological activity of the seed of wheat plants [ 117 ]. Similarly, [ 118 ] identified 180 carbonylated proteins in ABA-treated Arabidopsis thaliana leaves using affinity chromatography that differentially regulated stomatal closure upon ABA supplementation.…”
Section: Crosstalk Between Ros/rns/rss In Plant Defensementioning
confidence: 99%
“…Take 200 g seeds and place them in an environment of 50°C and 55% relative humidity to artificially aging for 42 days, and the germination rate was 12%. At least three independent experiments were performed in the determination of germination rate (Li et al, 2022).…”
Section: Wheat Seed and Artificial Aging Treatmentmentioning
confidence: 99%